(untitled) (Journal of the College of Basic Education, 2025)
The researcher used the experimental two-group experimental method with post-test testing. The sample of the research was 15 students from the Fourth grade for exeprimental group and 15 students control group . Statitcal methods were used Target current search to Designing instructional plans for the elements of the technical work to develop the skills of the Art students in the Fourth grade and using the appropriate educational Results showed the superiority of the single experimental group in the cognitive and skill test.